It's Complicated: Marital Ambivalence on Ambulatory Blood Pressure and Daily Interpersonal Functioning. Issue 5 (12th May 2015) - Birmingham, Wendy C.; Uchino, Bert N.; Smith, Timothy W.; Light, Kathleen C.; Butner, Jonathan
Abstract: Background: Marriage decreases cardiovascular morbidity although relationship quality matters. While some marriages contain highly positive aspects (supportive), marriages may also simultaneously contain both positive and negative aspects (ambivalent). Individuals whose spouses or own behavior is ambivalent may not experience the same cardiovascular-protective benefits of marriage. Purpose: The purpose of this study is to elucidate the physiological pathways by which marital quality may influence long-term health and examine ambivalent behavior on interpersonal-functioning and ambulatory blood pressure (ABP). Methods: Interpersonal functioning and ABP were examined in 94 couples. Results: Spousal and own ambivalent behavior was associated with lower intimacy ( ps < .01) and higher systolic ABP ( ps < .01). Spousal ambivalent behavior was associated with lower ratings of partner responsiveness ( p < .01) and less self- and spousal-disclosure ( ps < .05). Mediational analyses indicated that own behavior mediated links between spousal ambivalent behavior and ABP. Conclusions: Despite the positivity in relationships, individuals whose spouses' or own behavior is ambivalent may not receive cardiovascular protection from this positivity.